Protoberberine Isoquinoline Alkaloids from Arcangelisia gusanlung - Ling-Ling Yu; Rong-Tao Li; Yuan-Bao Ai; Wei Liu; Zhang-Shuang Deng; Zhong-Mei Zou (Molecules, 2014)
HPLC-DAD-directed isolation and purification of the methanol extract of stems of Arcangelisia gusanlung H. S. Lo. led to the isolation of a new protoberberine alkaloid, gusanlung E (1), along with fourteen known derivatives 2–15, seven of which were obtained from the genus Arcangelisia for the first time. The structures and absolute stereochemistry of these compounds were elucidated on the basis of spectroscopic analyses, including 1D and 2D NMR, mass spectrometry, and CD analyses. Gusanlung E (1) expressed weak cytotoxic activity against the SGC 7901 cell line with an IC50 value of 85.1 µM.